Kajian Semula Tapak 23, Kompleks Percandian Pengkalan Bujang, Kedah - Adam, Azman (2021)
The archaeological research at the Kompleks Percandian Pengkalan Bujang especially at site 23 aims to resolve issues related to function and cronometric dating, while complementing this complex data